PENGARUH PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI MTS AHMAD YANI JABUNG - Irna Nur Solikah; Imam Athoir Rokhman (STAI Ma'had Aly Al-Hikam Malang, 2024)
One of the problems found at MTs Ahmad Yani Jabung is the lack of understanding and ability of students in understanding Islamic Religious Education lessons, especially zakat material. One of the proposed models is discovery learning, which is known to train students' abilities in critical, analytical, and creative thinking. The purpose of this research is to know: (1) to know the effect of the discovery learning model on improving student learning outcomes in fiqh material at MTS Ahmad Yani Jabung. (2) to know the students' response to the discovery learning learning model. The research method used is a quantitative approach with the type of quasi-experimental design using two classes, the first class using the lecture model and the second class using the discovery learning model on the same material using tests. The results showed that the use of discovery learning model has a significant effect on students' learning outcomes in zakat material. Through paired t-test between pre-test and post-test in the experimental class, it was found that the significance value (2-tailed) was 0.000, smaller than 0.05, which indicated a significant difference between students' learning outcomes before and after using the discovery learning model. This confirms the positive influence of this learning model on students' understanding of fiqh material. In addition, students' responses to the discovery learning model were also positive, with a high percentage of satisfaction, indicating that students at MTs Ahmad Yani Jabung liked the use of this learning model.